-(7x+3)-(-6x-8)=2

Simple and best practice solution for -(7x+3)-(-6x-8)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7x+3)-(-6x-8)=2 equation:


Simplifying
-1(7x + 3) + -1(-6x + -8) = 2

Reorder the terms:
-1(3 + 7x) + -1(-6x + -8) = 2
(3 * -1 + 7x * -1) + -1(-6x + -8) = 2
(-3 + -7x) + -1(-6x + -8) = 2

Reorder the terms:
-3 + -7x + -1(-8 + -6x) = 2
-3 + -7x + (-8 * -1 + -6x * -1) = 2
-3 + -7x + (8 + 6x) = 2

Reorder the terms:
-3 + 8 + -7x + 6x = 2

Combine like terms: -3 + 8 = 5
5 + -7x + 6x = 2

Combine like terms: -7x + 6x = -1x
5 + -1x = 2

Solving
5 + -1x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -1x = 2 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = 2 + -5
-1x = 2 + -5

Combine like terms: 2 + -5 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| -1y=-20 | | 2p^2+4p-1=7p^2-7p+1 | | -3(4x-1)-3=-2(9x+11)-2 | | 1/4(x-3/8)=1/8 | | 3(2x+5)=2(3x-4) | | 1d/4=-2/4 | | -7+5y=-16 | | 3(3x-6)-18=-3(5x+5)-4 | | -9=-3y-7x | | -8x-y=-6 | | 0.3x+3.8=x | | 33.8-32= | | -9x+3y=9 | | -7x+5=-16 | | 1/9c+36=7/9c+5 | | -2+x/3=5 | | -30=5a | | 6(7b-7)=-4+4b | | y=0.8x+3 | | 2/3(12-3h)=h | | 7d+4d-6d+2-8=2d | | 3y=-4x+12 | | -7(1+2x)=23-8x | | -3(3x-6)-18=-3(5s+5)-4 | | -4(1+7m)=30+6m | | n=250/100(2) | | 4(k-9)+18=6 | | -8a^2-6a+9=0 | | -y+2=0 | | 4n+4/2=-13 | | y=0.9x+3 | | 1.92+.04x=1.92+.08x |

Equations solver categories